2020
DOI: 10.1098/rstb.2019.0720
|View full text |Cite
|
Sign up to set email alerts
|

Demographic uniformitarianism: the theoretical basis of prehistoric demographic research and its cross-disciplinary challenges

Abstract: A principle of demographic uniformitarianism underpins all research into prehistoric demography (palaeodemography). This principle—which argues for continuity in the evolved mechanisms underlying modern human demographic processes and their response to environmental stimuli between past and present—provides the cross-disciplinary basis for palaeodemographic reconstruction and analysis. Prompted by the recent growth and interest in the field of prehistoric demography, this paper reviews the principle of demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…The oscillations could even increase in range, resulting in extinction. Moreover, demographic studies of present-day forager groups showed that they were expanding at very fast rates, incompatible with evidence that over the long-term, hunter-gatherer populations were at very low levels, the socalled 'forager population paradox', discussed here by French & Chamberlain [38] and Tallavaara & Jørgensen [33]. The former also draw attention to another paradox in archaeological demography.…”
Section: Populations In Fluxmentioning
confidence: 56%
“…The oscillations could even increase in range, resulting in extinction. Moreover, demographic studies of present-day forager groups showed that they were expanding at very fast rates, incompatible with evidence that over the long-term, hunter-gatherer populations were at very low levels, the socalled 'forager population paradox', discussed here by French & Chamberlain [38] and Tallavaara & Jørgensen [33]. The former also draw attention to another paradox in archaeological demography.…”
Section: Populations In Fluxmentioning
confidence: 56%
“…observed in data (8,11). As such, uniformitarian assumptions of ecological and demographic equivalence in the past and present can be considered uniformitarian principles (25,26).…”
Section: Modeling Ethnographic Datamentioning
confidence: 99%
“…R. Soc. B 376: 20190707 foundations-the assumption that both demographic processes and biological markers for inferring age and sex are universal across human populations and through time [58,59].…”
Section: (C) Osteological Proxies (Skeletal Palaeodemography)mentioning
confidence: 99%
“…A good case in point is the 'forager population paradox' [76]; the differences in population growth rate estimates between those recorded among recent hunter-gatherers and those estimated for prehistoric huntergatherers based on back-projections of known global population sizes. One possible solution to this paradox is that prehistoric and recent hunter-gatherers are demographically different (although as French & Chamberlain [59] show, this interpretation violates the principle of demographic uniformitarianism that underlies all palaeodemographic research). A more persuasive solution, as presented by Tallavaara & Jørgensen [42] in this volume, relates to the differences in temporal scale inherent in the data on population growth rate(s) of past and present hunter-gatherers.…”
Section: Looking Forward: Grand Challenges For Palaeodemographymentioning
confidence: 99%